Tantangan dan Upaya Penerapan Kurikulum Merdeka di Era Digital: Literatur Review - Setiyadi, Muhammad Wahyu; Ardiansyah , Ardiansyah; Muharyati, Yully; Komalasari, Lala Intan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The challenges and efforts to implement the Independent Curriculum in the digital era in Indonesia require a multifaceted approach that discusses issues related to human resources, infrastructure, technology adaptation, and curriculum design. This research aims to identify the challenges and efforts faced in the implementation of the Independent Curriculum in Indonesia in the digital era through literature studies. This research uses a qualitative approach with a literature study method, this study examines various scientific articles, books, research reports, and education policies from the Indonesian Ministry of Education and Culture. The results show that the implementation of the Independent Curriculum faces several major challenges, including the digital divide, the readiness of human resources, and the need to strengthen the cooperation network between education units and related stakeholders. To overcome these challenges, various efforts need to be made, such as the development of technological infrastructure, strengthening the competence of teaching staff, and curriculum and learning reform. This study provides an important overview of the steps that need to be taken to optimize the implementation of the Independent Curriculum in the digital context in Indonesia.